Nonadiabatic electron gun at an electron beam ion source: commissioning results and charge breeding investigations - Pahl, Hannes; Bidault, N.; Khatri, G.; Pikin, A.; Wenander, F. J. C. (Physical review accelerators and beams, 2022)
The electron gun of the REXEBIS charge breeder at the REX/HIE-ISOLDE facility at CERN has been upgraded from a standard magneto-immersed type to a gun using a nonadiabatic magnetic element. The results from the cathode emission and electron beam propagation tests are presented, as well as the charge breeding efficiency for the new design. Complete mass-scans of the extracted beam have been performed from which the level of cathode-originating contaminations could be established, as well as partial pressures of the most abundant residual gases in the ion trapping region. Furthermore, optimal breeding times for a broad range of elements and charge states, either introduced as a gas or externally injected as singly charged ions into the trapping region, are given for different electron currents. From these values, effective electron current densities have been derived. Finally, the axial ion energy distributions of various elements and charge states were also measured, and the derived ion temperatures were correlated with the ion and electron beam overlap factors.
Gesehen am 16.09.2022